Resistance Exercise Evokes Changes on Urinary Bladder Function and Morphology in Hypoestrogen Rats - Magaldi, Fernanda M.; Moreno, Monise; Magaldi, Cristiane M.; Cafarchio, Eduardo M.; Aronsson, Patrik; Sato, Monica A.; Maifrino, Laura B. M. (Frontiers in Physiology, 2020)
Serum levels of estrogen decrease at climacterium and directly interfere with the urogenital tract. Urinary bladder (UB) is responsive to hormonal changes, especially estrogen. Resistance exercise elicits benefits on severe chronic diseases. Nevertheless, it is still unclear whether the resistance exercise directly affects the UB in ovariectomized (OVx) rats. This study focused to investigate the effects of resistance exercise on UB function and morphology in OVx and control rats. Adult female Wistar rats (~250-300 g, 14-16 wks-old) control (N=20) and OVx (N=20) were divided in the following groups: sedentary (SED), and trained over 1 wk (acute), 3 wks (intermediate), and 10 wks (chronic). Training was carried out in a ladder, with 6 bouts in alternate days with 75% of body weight load attached to the tail of the animal. Afterwards, the animals were isoflurane anesthetized for evaluation of intravesical pressure (IP) changes upon topical administration of acetylcholine (Ach) and noradrenaline (NE) on the UB. At the end of the experiment, the UB was harvest for histological analysis and stained with hematoxylin-eosin and Picrosirius Red. Acetylcholine increased the IP both in OVx and control rats, whereas NE decreased the IP. However the acute and intermediate groups showed attenuated responses to Ach and NE, whilst the chronic groups recovered the responses to Ach and NE close to those observed in SED groups. Acute and intermediate groups also showed decreased thickness of the muscular layer, with a reversal of the process with chronic training. In the OVx groups, the acute training reduced the thickness of the smooth muscle and mucosal layers, whereas the chronic training increased it. Urothelium thickness decreased in the OVx SED and acute groups. Collagen type I fibers (CI-F) reduced in OVx SED acute and intermediate groups, whilst collagen type III fibers (CIII-F) increased in the OVx acute group. In the mucosal layer, volume density of CFs reduced in OVx rats compared to control groups and the chronic training caused their recovery. Our data suggest that chronic resistance exercise for 10 wks reversed the functional and morphological changes caused by hypoestrogenism.